EFFECT OF MODIFIED FIVE-STAGE LEARNING CYCLE STRATEGY USING RECIPROCAL METHOD ON LEARNING SOME BASIC HANDBALL SKILLS FOR STUDENTS - Dahham, Nahidh Abboud (Universitas Negeri Gorontalo, 2025)
Learning strategies play a vital role in enhancing students’ acquisition of fundamental sports skills. Traditional teaching approaches often fail to maintain student motivation and engagement, particularly in skill-based subjects such as handball. Therefore, this study aimed to examine the effect of the Modified Five-Stage Learning Cycle Strategy integrated with the Reciprocal Method on learning selected basic handball skills among preparatory school students. The research employed an experimental design with two equivalent groups (experimental and control). The sample consisted of fourth preparatory grade students at Al-Suwaira Boys’ Preparatory School during the academic year 2023–2024, with a total of 165 students across four sections. Statistical analysis was conducted using SPSS. The findings revealed that students in the experimental group who were taught using the Modified Five-Stage Learning Cycle Strategy with the Reciprocal Method showed significant improvement in passing and dribbling skills compared to their pre-test results and to the control group, as indicated by calculated t values exceeding the tabulated values at the 0.05 significance level.In conclusion, the study demonstrated that the application of the Modified Five-Stage Learning Cycle Strategy combined with the Reciprocal Method positively impacts students’ acquisition of basic handball skills. This approach fosters engagement, reduces boredom, and provides structured learning opportunities that enhance skill development. The contribution of this research lies in offering practical evidence for integrating innovative instructional strategies into physical education curricula. It recommends that educators adopt this combined method to achieve better learning outcomes in handball and potentially extend its application to other skill-based sports education contexts.